GENDER IN EFL CLASSROOM: TRANSITIVITY ANALYSIS IN ENGLISH TEXTBOOK FOR INDONESIAN STUDENTS - Emilia, Emi; Moecharam, Nicke Yunita; Syifa, Iva Laela (Indonesian Journal of Applied Linguistics, 2017)
This paper is concerned with the topic of gender in EFL classroom, particularly in Indonesian context. Owing to the framework proposed by Sunderland (1992), the paper focuses on the discussion of gender in classroom materials, i.e. English textbooks. Selected reading passages were analyzed within the framework of Transitivity system of functional grammar (Halliday Mathiessen, 2004; Haliday Mathiessen, 2014). The Processes in the texts (e.g. travel, walk, and climb) reveal that males were perpetually constructed as ‘adventurous’, ‘risk taker’, ‘active’, ‘independent’, and ‘capable’. Meanwhile, the Processes also indicate that the females were shaped as more ‘passive', ’expressive’, ‘nurturing’, and ‘unassertive’ than their male counterparts (Blackstone, 2003; Evans Davies, 2000). The findings suggest that the gender roles were presented in an asymmetrical manner. The paper provides recommendation in terms of how both teachers and students can develop gender awareness in the classroom practices through the use of the textbooks.